Mesoscale Surface Wind‐SST Coupling in a High‐Resolution CESM Over the KE and ARC Regions. (8th December 2021) - Tang, Zhijia; Zhang, Rong‐Hua; Wang, Hongna; Zhang, Shaoqing; Wang, Hong
Abstract: A strong positive correlation exists between mesoscale sea surface temperature (SST) and surface wind stress perturbations in the extratropical oceans, which is revealed by high‐resolution satellite but is difficult to be accurately simulated in low‐resolution coupled ocean‐atmosphere models. The extent to which the mesoscale coupling is captured in a high‐resolution Community Earth System Model (CESM‐HR) is assessed in this study, with a focus on two regions, the Kuroshio Extensions (KE) and Agulhas Return Current (ARC), respectively. Compared with satellite observations, it is found that the CESM‐HR can well depict the characteristics of the mesoscale air‐sea coupling, with its strength being comparable to that observed; but in the KE region, the simulated strength is only half of the observed during summer. Mechanisms for the atmospheric responses to mesoscale SST perturbations through the pressure adjustment (PA) and the downward momentum transport (DMT) are analyzed. The results highlight different mechanisms for controlling the atmospheric responses over the KE and ARC regions, which are regionally and seasonally dependent. In the ARC region, pronounced dipole patterns of sea surface pressure (SLP) and vertical velocity perturbation responses indicate that the DMT exerts a dominant effect in both winter and summer. In the KE region, monopole patterns show the main role played by the PA mechanism for the atmospheric adjustment in summer, while dipole patterns indicate the main role played by the DMT mechanism in winter. The weak coupling strength in summer over the KE is closely related to the inadequate parameterization of vertical heat mixing. Plain Language Summary: High‐resolution satellite observations show that wind stress is positively correlated with sea surface temperature (SST) at mesoscales (100–1, 000 km), and the regression coefficient of wind stress on SST is used to quantify the strength of the atmospheric response to mesoscale SST perturbations. The coupling strength simulated in low‐resolution coupled ocean‐atmosphere models is generally weaker than that observed. A high‐resolution Community Earth System Model (CESM‐HR), which captures the characteristics of mesoscale air‐sea interaction well, is utilized to explore the mechanisms for the atmospheric responses to SST perturbations in the Kuroshio Extensions (KE) and Agulhas Return Current (ARC) regions, respectively. The downward momentum transport (DMT) mechanism exerts a dominant effect in both winter and summer over the ARC region, with the related coupling strength being comparable to that observed. In the KE region, the DMT mechanism plays a dominant role during winter, while the pressure adjustment (PA) mechanism is the dominant player during summer with a weak coupling strength, being only half of the observed. As the PA mechanism is mainly manifested as vertical heat transport which adjusts sea surface air pressure, the weak coupling strength is suggestive of the inappropriate parameterization of vertical heat mixing in the atmospheric model. Key Points: The characteristics of mesoscale air‐sea coupling are well represented by a high‐resolution Community Earth System Model (CESM‐HR) The mechanisms for the atmospheric responses to mesoscale sea surface temperature perturbations are regionally and seasonally dependent The simulated weak coupling strength is mainly related to the inappropriate parameterization of vertical heat mixing in the atmosphere model